185k views
0 votes
Which of the following equations is the result of completing the square on x2 - 6x - 9 = 0? (x - 3)2 = 0 (x - 3)2 = 9 (x - 3)2 = 18

2 Answers

7 votes

Answer:

(x-3)² = 18

Explanation:

We have given an equation.

x²-6x-9 = 0

We have to find the equation after completing square.

Adding 9 to both sides of above equation, we have

x²-6x-9+9 = 0+9

x²-6x = 9

Adding half of the term -6 to both sides of above equation, we have

x²-6x+(-3)² = 9+(-3)²

(x-3)² = 9+9

(x-3)² = 18 which is the answer.

User Mahdi Yusuf
by
5.9k points
6 votes

Answer:


(x-3)^2=18

Explanation:

The given equation is;


x^2-6x-9=0

Group the constant on the Right Hand Side.


x^2-6x=9

Add half the square of the coefficient of
x to both sides.


x^2-6x+(-3)^2=9+(-3)^2

The left hand side is now a perfect square.


(x-3)^2=9+9


(x-3)^2=18

User Kirqe
by
5.9k points